Kualitas Fisik Silase Jerami Jagung (Zea mays) dengan Campuran Indigofera zollingeriana - Dianita, Rahmi; Andriani, Shilvi; Devitriano, Dodi; Musnandar, Endri; Darlis, Darlis; Syafwan, Syafwan (Universitas Batanghari Jambi, 2024)
Corn straw has the potential as a ruminant feed, but is constrained by low crude protein so it must be combined with Indigofera zollingeriana legumes which have high crude protein. The addition of Indigofera zollingeriana at different levels is expected to increase the crude protein of corn straw silage (Zea mays) and is expected to produce good silage quality. This study aims to determine the physical quality of corn straw silage (Zea mays) and Indigofera zollingeriana in different proportions. The variables observed in this study were the percentage of shrinkage, pH value, percentage of moldy silage, fleigh value, and physical quality (color, aroma, and texture). This experiment was arranged in a Completely Randomized Design (CRD) with 3 treatments and each treatment was repeated 6 times, so there were 18 experimental units, namely P1 = 80% Corn straw + 15% Indigofera zollingeriana + 4% bran + 1% mineral mixture; P2 = 70% Corn straw + 25% Indigofera zollingeriana + 4% bran + 1% mineral mixture; P3 = 60% Corn straw + 35% Indigofera zollingeriana + 4% bran + 1% mineral mixture. The results of the analysis of variance test showed that corn straw silage (Zea mays) with a mixture of Indigofera zollingeriana had no significant effect (P>0.05) on the percentage of moldy silage, fleigh value, and physical quality (color, aroma, texture) but had a significant effect (P<0.05) on the percentage of shrinkage and pH of silage. Based on this study, it can be concluded that the best silage proportion was obtained in the P2 treatment with 70% corn straw + 25% Indigofera zollingeriana + 4% fine bran + 1% mineral mixture, resulting in good quality silage.